Structural properties of the electropulse phenomena of heat and mass exchange in non-uniform liquid - Sakipova, S.E. (Ye.A.Buketov Karaganda State University Publishing house, 2010)
Paper shows the opportunity of describing nonlinear properties of heat and mass exchange processes in a non-uniform liquid at pulse influence based on research behavior of open system, which is capable to self-organize structures. The formulas to calculate polytrope parameter received, and, there are considered change of structural and dynamic properties of a non-uniform liquid at change of gas concentration.
Keywords: heat and mass exchange; non-uniform liquid; self-organize structures; polytrope parameter